Study of Blasting Parameters Optimization of Underground Powerhouse of Pumped Storage Project with Flac3D Numerical Simulation Method - Wan, Sheng; Zhu, Yuhong; Li, Hui (Journal of physics. Conference series, 2019)
Based on optimization from Mohr-Coulomb constitutive model, FLAC3Dprocedure is used to simulate the excavation of Qingyuan pumped storage power station. By adding the monitoring simulation, the consequence reveals that the minimum main stress is mainly distributed in the center place of top and base of goaf. At the beginning of excavation, the rock stratum in the center of exposed surface of top of goaf is mostly tensed which causes tensile stress failure characteristics easily, and meanwhile, the skewback of top arch and other corners are easily occur shear failure, following with the excavation proceeding, the main failure form of rock stratum is changing to shear failure on partial corners. This paper mainly discusses on the blasting parameters optimization by adapting the kerve step blasting from "-" type to "V" type. Our practice might as well serve as a reference for similar projects to come.